Uranium-Lead LA-ICPMS analysis of calcite sample Vendee_PP5 from the Vendée coast - Bouat, Loic (In: Bouat, L (2024): Uranium-Lead LA-ICPMS analysis of calcite samples from the Vendée coast [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.948396, 2024)
This data provide all details concerning LA-ICPMS U-Pb analyzis on calcites from the Vendée coast in France. The 3 calcites samples PP5, PN201 and ASN201 come from veins hosted in the sedimentary cover below the unconformity with the Armorican Massif below. The LA-ICPMS U-Pb analyzis were proceed with the GeOHeLiS Platform from Université Rennes 1 (France) using WC1 standard as quality control.
Keywords: Calcite; dating; U-Pb dating